PEDAGOGIC CONCEPTS OF EXPOSED CHILDREN OF DRUG USERS: STUDY AT THE AR-RAHMAN PONDOK, PALEMBANG - Sahrizal Sahrizal; Akmal Hawi; Ahmad Zainuri; Ari Sandi (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
Drug abuse is a way of straying alienated from society. Every drug addict who completes the rehabilitation period still avoids rejection of the insurance he has and impacts others as his social environment. Therefore, the purpose of this study is to describe the application of pedagogical concepts in the application of the self-concept of children who use drugs in the Pondok Ar-Rahman Islamic Boarding School in Palembang. This type of research is qualitative with a case study. The informants of this study were students of former drug users, teachers, and students. Data collected using observation, interviews, and documentation, then analyzed using case study data analysis. The results showed that the self-concept factors of ex-drug user students felt a sense of approval and were easily fooled by friends. Regret and desire to improve themselves create an image supported by the support, family, and teachers. Contrary to self-concept is a matter of learning, the feeling of fear of being bullied, and not yet free from feelings of guilt. Positive self-concept of students is also supported by approval, motivation, and acceptance of assistance and school attendance to self-actualize through religious discussions, a strong willingness to overcome memories of his past through positive activities of performing five daily prayers, reciting, listening to lectures, and exercise and take part in sports extracurriculars at school.